1994
DOI: 10.1152/ajpcell.1994.267.3.c738
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Na+ channels in the response of carotid body chemoreceptor cells to hypoxia

Abstract: The role played by Na+ channels of carotid body (CB) chemoreceptor cells was investigated by studying the effects of tetrodotoxin (TTX) on the release of 3H-labeled catecholamines ([3H]CA) by adult rabbit CBs previously incubated with the precursor [3H]tyrosine. TTX inhibited partially the release of [3H]CA elicited by mild hypoxia (10 or 7% O2) or by depolarizing incubation medium containing 20 or 30 mM KCl, but the response to more intense hypoxia (5 or 2% O2) or to higher KCl concentration (40 or 50 mM) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
1
9
0
5
Order By: Relevance
“…Obeso et al [24,25] showed that nitrendipine, a blocker of voltage-dependent Ca2+ channels, at a concentration of 0.5 pM, reduced by nearly 90% the release of DA elic ited by high external K+ and by nearly 85% that elicited by a moderate hypoxic stimulus, and Rocher et al [26] showed that veratridine, an activator of voltage-dependent Na+ channels elicited a release of DA which was dependent on the presence of Na+ and Ca2+ in the incubating solution and was completely blocked by tetrodotoxin (TTX; a blocker of Na+ channels). More recently it has also been shown that TTX partially blocks the release of DA elicited by hypoxia [27], Summarizing these findings, at the beginning of 1988 we had learnt that chemoreceptor cells are excita ble, that they possess a membrane potential dependent on K+, that they possess Na+, and Ca2+ channels operated by voltage, that low PO2 must depolarize chemoreceptor cells as a prerequisite to activate voltage-dependent Na+ and Ca2+ channels and that influx of Ca2+ required by hypoxia to elicit the release of DA occurs via voltage-dependent Ca2+.…”
Section: Membrane Model O F Oxygen Chemoreceptionmentioning
confidence: 98%
“…Obeso et al [24,25] showed that nitrendipine, a blocker of voltage-dependent Ca2+ channels, at a concentration of 0.5 pM, reduced by nearly 90% the release of DA elic ited by high external K+ and by nearly 85% that elicited by a moderate hypoxic stimulus, and Rocher et al [26] showed that veratridine, an activator of voltage-dependent Na+ channels elicited a release of DA which was dependent on the presence of Na+ and Ca2+ in the incubating solution and was completely blocked by tetrodotoxin (TTX; a blocker of Na+ channels). More recently it has also been shown that TTX partially blocks the release of DA elicited by hypoxia [27], Summarizing these findings, at the beginning of 1988 we had learnt that chemoreceptor cells are excita ble, that they possess a membrane potential dependent on K+, that they possess Na+, and Ca2+ channels operated by voltage, that low PO2 must depolarize chemoreceptor cells as a prerequisite to activate voltage-dependent Na+ and Ca2+ channels and that influx of Ca2+ required by hypoxia to elicit the release of DA occurs via voltage-dependent Ca2+.…”
Section: Membrane Model O F Oxygen Chemoreceptionmentioning
confidence: 98%
“…She showed further that veratridine induced release was nearly abolished by TTX, and most important, that low PO 2 -induced release also was partially inhibited by TTX. Her findings were communicated in early in 1987 to the Spanish Society of Biophysics, published as a short note in 1988 and as full length paper in 1994 [61,62,63]. Table 1 presents the status of our knowledge by the fall of 1987.…”
Section: The Advances In the Cellular Physiology Of The Cb 1984–19mentioning
confidence: 99%
“…It should also be noted from Table 1 that even if Na + channels participate in the cascade of events that occurs between the low PO 2 detection and the neurosecretory response [63], this participation represents an amplifying signal because an important part of the response (≈60%) still remains when Na + channels are fully inhibited. Additionally, Table 1 shows that the participation of dihydropyridine sensitive channels in the entry of Ca 2+ to support hypoxia-induced release varies with the intensity of hypoxia, and finally, that even with mild hypoxia, some voltage-dependent pathways additional to L-type Ca 2+ channels participate in the stimulus- secretion coupling, because at any given hypoxic intensity the evoked release of DA is Ca 2+ dependent by more than 95%.…”
Section: The Advances In the Cellular Physiology Of The Cb 1984–19mentioning
confidence: 99%
“…Na + currents play a major role in the magnitude of the secretory response of mature, rabbit carotid bodies to moderate hypoxia [24], and it was suggested that this current was not present in fetal cells [15]. Na + currents play a major role in the magnitude of the secretory response of mature, rabbit carotid bodies to moderate hypoxia [24], and it was suggested that this current was not present in fetal cells [15].…”
Section: Cellular Basis Of Chemotransductionmentioning
confidence: 99%
“…Previous studies have shown that the fast Na + current in rabbit glomus cells may play a major role in mediating depolarization [11,25], and can modulate the magnitude of catecholamine secretion in response to hypoxic stimuli [24]. We also began to address the cellular basis of developmental changes by examining age-dependent changes in the magnitude of Na + and Ca 2+ currents in isolated rabbit glomus cells.…”
Section: Introductionmentioning
confidence: 99%